Fluorine-based lubricant, electrode, and secondary battery
Patent Information
- Application Number
- JP2023127472
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-04
- Publication Date
- 2025-02-17
AI Technical Summary
【0013】 本開示においては、電極の剥がれを抑制できるフッ素系潤滑剤を提供できるという効果を奏する。
Smart Images

Figure 2025023394000001_ABST
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a fluorine-based lubricant, an electrode, and a secondary battery. [Background technology]
[0002] Batteries such as lithium ion secondary batteries include electrodes having a current collector and an active material layer. For example, Patent Document 1 discloses a negative electrode composite layer for an all-solid-state lithium ion secondary battery, which contains porous silicon particles as a negative electrode active material and a sulfide-based solid electrolyte. Patent Document 2 discloses that an electrolyte (electrolytic solution) contained in the active material layer is an electrolyte solution containing an alkali metal salt dissolved in a nonaqueous solvent containing perfluoroether. Patent Document 3 discloses an electrode containing a perfluoropolyether group-containing compound on the surface. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2020-170605 A [Patent Document 2] JP 2018-200866 A [Patent Document 3] JP 2018-147887 A Summary of the Invention [Problem to be solved by the invention]
[0004] In an active material layer containing an active material and a sulfide solid electrolyte, the active material contained in the active material layer expands and contracts due to charging and discharging. If the volume change of the active material layer is large, the interfaces of the active material particles may peel off from each other, and the electrodes may peel off. If the electrodes peel off, the battery resistance may increase and the battery performance may deteriorate. In particular, active materials containing Si (Si-based active materials) are effective in increasing the energy density of batteries, but they are prone to the above-mentioned deterioration in battery performance due to large volume change due to charging and discharging.
[0005] The present disclosure has been made in view of the above-mentioned circumstances, and has as its main object to provide a fluorine-based lubricant capable of suppressing peeling of electrodes. [Means for solving the problem]
[0006] [1] A fluorine-based lubricant that is used in an active material layer that contains an active material and a sulfide solid electrolyte and is solid at 25°C.
[0007] [2] The fluorine-based lubricant according to [1], having a melting point of 120°C or lower.
[0008] [3] The fluorine-based lubricant according to [1] or [2], having a fluoropolyether structure.
[0009] [4] An electrode having an active material layer and a current collector, the active material layer containing a Si-based active material, a sulfide solid electrolyte, and a fluorine-based lubricant, the fluorine-based lubricant being the fluorine-based lubricant according to any one of [1] to [3].
[0010] [5] The electrode according to [4], wherein the Si-based active material and the solid fluorine-based lubricant are composited.
[0011] [6] The electrode according to [4] or [5], wherein a ratio of the fluorine-based lubricant to the Si-based active material is 4% by weight or more and 12% by weight or less.
[0012] [7] A secondary battery comprising the electrode according to any one of [4] to [6]. Effect of the Invention
[0013] The present disclosure has an effect of providing a fluorine-based lubricant that can suppress peeling of electrodes. [Brief description of the drawings]
[0014] [Figure 1] 1 is a schematic cross-sectional view illustrating a secondary battery according to the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] The fluorine-based lubricant, electrode, and secondary battery according to the present disclosure will be described in detail below. Here, in the present disclosure, the term "fluorine-based lubricant" refers to a lubricant that contains fluorine (F).
[0016] A. Fluorine-based lubricants The fluorine lubricant in the present disclosure is used in an active material layer containing an active material and a sulfide solid electrolyte, and is a solid at 25° C. The active material, the sulfide solid electrolyte, and the active material layer will be described later.
[0017] As described above, active materials expand and contract when charged and discharged, and the volume change is particularly large in Si-based active materials. Therefore, there is a risk that the electrode using the active material may peel off. However, it is presumed that the fluorine-based lubricant in the present disclosure penetrates into the gap where the interface between the active materials peels off, and as a result, it is thought that the peeling of the electrode can be suppressed (the peeling can be repaired).
[0018] The melting point of the fluorine-based lubricant is, for example, 38°C or higher, may be 50°C or higher, may be 65°C or higher, or may be 80°C or higher. On the other hand, the melting point of the fluorine-based lubricant is, for example, 200°C or lower, may be 150°C or lower, or may be 100°C or lower. By having the above melting point, even if the interface between active materials peels off due to the expansion and contraction of the active materials, the fluorine-based lubricant undergoes a phase transition to a liquid due to heat caused by charging and discharging the battery or by heating the battery, and functions as a lubricant between the active materials to repair the peeling, and it is considered that an increase in battery resistance can be suppressed. In particular, the melting point of the fluorine-based lubricant is preferably in the range of 60°C or higher and 120°C or lower. Here, the melting point of the fluorine-based lubricant can be determined as the temperature corresponding to the maximum value in the heat of fusion curve when the temperature is increased at a rate of 5°C / min using a differential scanning calorimetry (DSC) device.
[0019] Fluorine-based lubricants usually contain at least one of a fluoroalkyl group and a fluoroalkylene group. The fluoroalkyl group may be a functional group in which all hydrogen atoms in an alkyl group are replaced with fluorine (perfluoroalkyl group), or may be a functional group in which some hydrogen atoms in an alkyl group are replaced with fluorine. The number of carbon atoms in the fluoroalkyl group may be, for example, 1 to 10, or 1 to 5. The number of carbon atoms in the fluoroalkylene group may be, for example, 1 to 20, or 1 to 15. The fluorine-based lubricant may have a straight chain structure or a branched chain structure. The fluorine-based lubricant may or may not have an ether bond in the main chain. The terminal functional group located at the end of the fluorine-based lubricant is not particularly limited. Examples of the terminal functional group include a fluorine group, a hydrogen group, a hydroxyl group, an aldehyde group, a carboxylic acid group, a C1-10 alkyl ester group, an amide group which may have one or more substituents, and an amino group which may have one or more substituents.
[0020] An example of the fluorine-based lubricant is a carboxylic acid compound containing at least one of a fluoroalkyl group and a fluoroalkylene group. The carbon numbers of the fluoroalkyl group and the fluoroalkylene group are as described above. The carboxylic acid compound may have one carboxy group, two carboxy groups, or three or more carboxy groups. Examples of the carboxylic acid compound include the following compounds. HOOC-(CF2)2-COOH HOOC-(CF2)3-COOH HOOC-(CF2)4-COOH HOOC-CF2O(CF2)2OCF2-COOH CF3(CF2) 10 -COOH CF3(CF2) 12 -COOH
[0021] Other examples of fluorine-based lubricants include alcohol compounds containing at least one of a fluoroalkyl group and a fluoroalkylene group. The carbon numbers of the fluoroalkyl group and the fluoroalkylene group are as described above. The alcohol compounds may have one hydroxyl group, two hydroxyl groups, or three or more hydroxyl groups. Examples of the alcohol compounds include the following compounds. HO―CH2(CF2)2CH2―OH HO―CH2(CF2)3CH2―OH HO―CH2(CF2)4CH2―OH HO―CH2CF2O(CF2)2OCF2CH2―OH CF3(CF2) 13 -OH
[0022] Other examples of fluorine-based lubricants include fluoroalkanes. The number of carbon atoms in the fluoroalkanes is, for example, from 10 to 20. Examples of the fluoroalkanes include the following compounds. CF3(CF2) 11 CF3 CF3(CF2) 14 CF3 CF3(CF2) 18 CF3
[0023] Other examples of fluorine-based lubricants include ester compounds containing at least one of a fluoroalkyl group and a fluoroalkylene group. The carbon numbers of the fluoroalkyl group and the fluoroalkylene group are as described above. Among them, the carbon number of the fluoroalkylene group is preferably 8 or more and 15 or less. The ester compound may have one ester group, two ester groups, or three or more ester groups. Examples of the ester compound include the following compounds. CH3OOC―(CF2) 10 -COOCH3 CF3(CF2) 12 -COOCH3
[0024] Furthermore, examples of fluorine-based lubricants include compounds having a fluoropolyether structure (FPE structure). The compound having a fluoropolyether structure (FPE structure) has a structure represented by the following formula (1). E1-Rf1-RF-O-Rf2-E2 (1) [In formula (1), Rf1 and Rf2 each independently represent a C1-16 divalent alkylene group optionally substituted by one or more fluorine atoms, E1 and E2 are each independently a monovalent group selected from the group consisting of a fluorine group, a hydrogen group, a hydroxyl group, an aldehyde group, a carboxylic acid group, a C1-10 alkyl ester group, an amide group which may have one or more substituents, and an amino group which may have one or more substituents; RF is -(AO) n - (A contains a carbon chain as a main chain and has at least one fluorine atom bonded to the carbon chain). The number of carbon atoms in the carbon chain of A is preferably, for example, 1, 2, 3 or 4. A may or may not have a hydrogen atom. In addition, A may have -CF 3-x H x (0≦x≦3). From the viewpoint of being a solid at 25° C., the RF may be -(CH2CF2CF2O) n - is preferred, where n is a number of 1 or more.
[0025] Among the above-mentioned compounds, compounds having a fluoropolyether structure are preferred because of their electrochemical stability and low volatility at high temperatures.
[0026] B. Electrode The electrode in the present disclosure is an electrode having an active material layer and a current collector, the active material layer containing an active material and a fluorine-based lubricant, and the fluorine-based lubricant is the fluorine-based lubricant described above.
[0027] According to the present disclosure, the active material layer in the electrode contains the above-mentioned fluorine-based lubricant, and thus the electrode is prevented from peeling off.
[0028] 1.Active material layer The electrode according to the present disclosure has an active material layer and a current collector. The active material layer contains an active material, a sulfide solid electrolyte, and a fluorine-based lubricant.
[0029] (1)Active material Examples of the active material include carbon-based active materials, oxide active materials, and metal active materials. Examples of the carbon-based active material include graphite. Examples of the oxide active material include lithium titanate. Examples of the metal active material include Si-based active materials. Among these, Si-based active materials are preferred. The Si-based active material contains at least the Si element. Examples of the Si-based active material include simple Si, Si alloys, and Si oxides. The Si alloy preferably contains the Si element as the main component. The ratio of the Si element in the Si alloy is, for example, 50 at% or more, may be 70 at% or more, or may be 90 at% or more. Examples of the Si alloy include Si-Li-based alloys, Si-Al-based alloys, Si-Sn-based alloys, Si-In-based alloys, Si-Ag-based alloys, Si-Pb-based alloys, Si-Sb-based alloys, Si-Bi-based alloys, Si-Mg-based alloys, Si-Ca-based alloys, Si-Ge-based alloys, and Si-Pb-based alloys. The Si alloy may be a binary alloy or a multi-component alloy having three or more components. The Si alloy may be a Si-Li alloy. Examples of the Si oxide include SiO.
[0030] The shape of the active material may be, for example, particulate. The average particle size (D 50 ) is, for example, 10 nm or more and 50 μm or less. 50 ) refers to the cumulative 50% particle size in the volume-based particle size distribution measured with a laser diffraction particle size analyzer.
[0031] The proportion of the active material in the active material layer is, for example, 50% by weight or more and 99% by weight or less.
[0032] (2) Sulfide solid electrolyte The sulfide solid electrolyte is usually an electrolyte containing sulfur (S) as a main component of an anion element. The sulfide solid electrolyte preferably contains, for example, Li element, X element (X is at least one of P, As, Sb, Si, Ge, Sn, B, Al, Ga, and In), and S element. The sulfide solid electrolyte may further contain at least one of O element and halogen element.
[0033] Examples of sulfide solid electrolytes include Li2S-P2S5, Li2S-P2S5-LiI, Li2S-P2S5-GeS2, Li2S-P2S5-Li2O, Li2S-P2S5-Li2O-LiI, Li2S-P2S5-LiI-LiBr, Li2S-SiS2, Li2S-SiS2-LiI, Li2S-SiS2-LiBr, Li2S-SiS2-LiCl, Li2S-SiS2-B2S3-LiI, Li2S-SiS2-P2S5-LiI, Li2S-B2S3, and Li2S-P2S5-Z. m S n (where m and n are positive numbers. Z is Ge, Zn, or Ga.), Li2S-GeS2, Li2S-SiS2-Li3PO4, Li2S-SiS2-Li x MO y (where x and y are positive numbers, and M is P, Si, Ge, B, Al, Ga, or In.)
[0034] The sulfide solid electrolyte may be glass (amorphous) or glass ceramics. The average particle size (D 50 ) is, for example, 0.01 μm or more and 10 μm or less.
[0035] The proportion (wt %) of the sulfide solid electrolyte in the active material layer is, for example, 10 wt % or more and 50 wt % or less.
[0036] (3) Fluorine-based lubricants The melting points and types of fluorine-based lubricants are the same as those described in "A. Fluorine-based lubricants", so the description here is omitted.
[0037] In the active material layer, the ratio of the fluorine-based lubricant to the active material is, for example, 4% by weight or more, or may be 6% by weight or more, or may be 8% by weight or more, while the ratio is, for example, 12% by weight or less, or may be 10% by weight or less.
[0038] In addition, in the active material layer, it is preferable that the active material and the solid fluorine-based lubricant are composited. For example, the active material that has been physically mixed by mechanical milling or the like and the solid fluorine-based lubricant are used as the active material. Whether the active material and the solid fluorine-based lubricant are composited or not can be confirmed by microscopic observation such as SEM (scanning electron microscope) and TEM (transmission electron microscope). It is considered that the composite of the active material and the solid fluorine-based lubricant forms an interface between the active materials better, and in particular, the resistance during the initial charge and discharge is suppressed.
[0039] (4) Active material layer The active material layer may contain at least one of a conductive assistant and a binder in addition to the above-mentioned active material, sulfide solid electrolyte, and fluorine-based lubricant.
[0040] Examples of the conductive assistant include carbon materials, such as particulate carbon materials such as acetylene black (AB) and ketjen black (KB), and fibrous carbon materials such as carbon fiber, carbon nanotube (CNT), and carbon nanofiber (CNF).
[0041] Examples of binders include rubber-based binders such as butadiene rubber (BR), acrylate butadiene rubber (ABR) and styrene butadiene rubber (SBR), as well as fluorine-containing binders such as polyvinylidene fluoride (PVDF) and polytetrafluoroethylene (PTFE).
[0042] The thickness of the active material layer is not particularly limited, but is, for example, 0.1 μm or more and 1000 μm or less. The active material layer may be a positive electrode active material layer or a negative electrode active material layer. That is, the electrode in the present disclosure may be a positive electrode or a negative electrode.
[0043] 2. Current collector The current collector is a member having a function of collecting electrons from the active material layer. The current collector may be a positive electrode current collector or a negative electrode current collector. Examples of the material of the current collector include metals such as aluminum, copper, SUS, and nickel. Examples of the shape of the current collector include a foil shape and a mesh shape.
[0044] 3. Electrode The electrodes of the present disclosure are typically used in secondary batteries, which are described below.
[0045] B. Secondary battery FIG. 1 is a schematic cross-sectional view illustrating a secondary battery according to the present disclosure. The secondary battery 100 shown in FIG. 1 has a positive electrode 10A having a positive electrode current collector 1a and a positive electrode active material layer 2a, a negative electrode 10B having a negative electrode current collector 1b and a negative electrode active material layer 2b, and an electrolyte layer 11 disposed between the positive electrode 10A and the negative electrode 10B. The secondary battery 100 includes the electrodes described above. Specifically, at least one of the positive electrode 10A and the negative electrode 10B in the secondary battery 100 corresponds to the electrode described in "A. Electrode" above.
[0046] According to the present disclosure, since the secondary battery includes the above-mentioned electrode (electrode in which peeling is suppressed), the secondary battery is one in which an increase in resistance due to peeling of the electrode is suppressed.
[0047] 1. Positive electrode A secondary battery usually has a positive electrode. The positive electrode usually has a positive electrode current collector and a positive electrode active material layer arranged on the electrolyte layer side of the positive electrode current collector. The positive electrode in the secondary battery preferably corresponds to the above-mentioned electrode. On the other hand, when the positive electrode in the present disclosure does not correspond to the above-mentioned electrode, the negative electrode in the present disclosure usually corresponds to the above-mentioned electrode. In this case, any conventional positive electrode can be used as the positive electrode.
[0048] 2.Negative electrode A secondary battery usually has a negative electrode. The negative electrode usually has a negative electrode current collector and a negative electrode active material layer arranged on the surface of the negative electrode current collector on the electrolyte layer side. The negative electrode in the secondary battery preferably corresponds to the above-mentioned electrode. On the other hand, when the negative electrode in the present disclosure does not correspond to the above-mentioned electrode, the positive electrode in the present disclosure usually corresponds to the above-mentioned electrode. In this case, any conventional negative electrode can be used as the negative electrode.
[0049] 3. Electrolyte layer The secondary battery usually has an electrolyte layer disposed between the positive electrode and the negative electrode. More specifically, the electrolyte layer is usually disposed between the positive electrode active material layer and the negative electrode active material layer. The electrolyte layer preferably contains the above-mentioned sulfide solid electrolyte as an electrolyte. In other words, the electrolyte layer is preferably a solid electrolyte layer.
[0050] 4. Secondary battery The secondary battery in the present disclosure is typically a lithium ion secondary battery. The secondary battery is preferably an all-solid-state battery containing a sulfide solid electrolyte as a solid electrolyte. The secondary battery is used, for example, as a power source for vehicles such as hybrid electric vehicles (HEVs), plug-in hybrid electric vehicles (PHEVs), electric vehicles (BEVs), gasoline automobiles, and diesel automobiles. In particular, it is preferably used as a driving power source for hybrid electric vehicles (HEVs), plug-in hybrid electric vehicles (PHEVs), or electric vehicles (BEVs). The secondary battery may also be used as a power source for moving bodies other than vehicles (for example, railways, ships, and aircraft), and may also be used as a power source for electrical products such as information processing devices.
[0051] The present disclosure is not limited to the above-described embodiment. The above-described embodiment is merely an example, and any configuration that is substantially the same as the technical idea described in the claims of the present disclosure and that exhibits similar effects is included in the technical scope of the present disclosure. EXAMPLES
[0052] [Synthesis Example 1] (Synthesis of Compound 1-1) In a reaction vessel substituted with nitrogen, 15.4 g of cesium fluoride, 290 mL of diglyme, and 107.0 g of methyl 2,2,3-trifluoro-3-oxopropanoate were added, and the mixture was stirred for 10 minutes at 5°C in an ice bath. 526.0 g of 2,2,3,3-tetrafluorooxetane was then added dropwise from the dropping funnel to the reaction vessel over 20 minutes at 5°C in an ice bath, and the mixture was stirred for 2 hours. The ice bath was then removed, and the mixture was stirred for 50 hours to obtain a reaction solution. 60 mL of methanol was added dropwise to the reaction solution over 20 minutes, and the mixture was stirred for 24 hours. Volatiles were then removed from the reaction solution under reduced pressure. Then, 80 g of m-xylene hexafluoride and 40 g of water were added, and the mixture was washed by separation, and 5 g of magnesium sulfate was added to the extracted organic layer and dried to obtain a treatment solution. The volatile matter was distilled off from the resulting treated solution to obtain compound 1-1 (a compound having an FPE structure) represented by the following chemical formula.
[0053] [ka]
[0054] [Comparative Example 1] In an organic solvent, a conductive additive, a binder, a sulfide solid electrolyte, and a positive electrode active material (LiNi 0.8 Co 0.15 Mn 0.05O2) was added and mixed using an ultrasonic homogenizer. This produced a positive electrode slurry. The positive electrode slurry was applied to a positive electrode current collector (Al foil) and dried to produce a positive electrode having a positive electrode current collector and a positive electrode active material layer. Note that butyl butyrate was used as the organic solvent, VGCF was used as the conductive additive, PVDF was used as the binder, and 10LiI-15LiBr-75Li3PS4 was used as the sulfide solid electrolyte. These same materials were used in the procedures described below.
[0055] Next, the conductive additive, binder, sulfide solid electrolyte, and negative electrode active material (Si particles) were added to the organic solvent and kneaded using an ultrasonic homogenizer. This resulted in a negative electrode slurry. The negative electrode slurry was applied to a negative electrode current collector (Cu foil) and dried to produce a negative electrode having a negative electrode current collector and a negative electrode active material layer.
[0056] Next, the binder and the sulfide solid electrolyte were added to the organic solvent and kneaded using an ultrasonic homogenizer. This resulted in a solid electrolyte layer slurry. The resulting solid electrolyte slurry was applied to a transfer foil (Al foil) and dried to produce a transfer member having a solid electrolyte layer and a transfer foil.
[0057] The positive electrode, the negative electrode, and the transfer member were molded into a rectangular shape. Then, the positive electrode and the transfer member were stacked so that the solid electrolyte layer and the positive electrode active material layer faced each other, and roll-pressed at 165°C and a pressure of 50 kN / cm. Then, the transfer foil of the transfer member was peeled off to prepare a positive electrode side structure. Also, the transfer member and the negative electrode were stacked so that the solid electrolyte layer and the negative electrode active material layer faced each other, and roll-pressed at 25°C and a pressure of 50 kN / cm. Then, the transfer foil of the transfer member was peeled off to prepare a negative electrode side structure.
[0058] The negative electrode side structure and the positive electrode side structure were punched out into circles with diameters of 13.00 mm and 11.28 mm, respectively. A sulfide solid electrolyte was added onto the solid electrolyte layer of the negative electrode side structure, and pressed using a uniaxial press. Then, the positive electrode side structure and the negative electrode structure were stacked so that the solid electrolyte layers faced each other to obtain a laminate. A current extraction tab was attached to the laminate, and the laminate was sealed in an aluminum laminate using a vacuum sealer. This produced an evaluation battery (all-solid-state battery).
[0059] [Examples 1 to 3] A battery for evaluation was prepared in the same manner as in Comparative Example 1, except that a fluorine-based lubricant (compound 1-1 having an FPE structure) was added to the organic solvent in the preparation of the negative electrode slurry. The amount of the fluorine-based lubricant added was such that the ratio (wt%) of the fluorine-based lubricant to the negative electrode active material (Si particles) was the value shown in Table 1. The melting point of the fluorine-based lubricant used was 66°C.
[0060] [Example 4] The Si particles and the solid-state fluorine-based lubricant were weighed out in the ratio shown in Table 1 and mixed in a mortar to prepare a composite. A battery for evaluation was prepared in the same manner as in Comparative Example 1, except that the above composite was used in the preparation of the negative electrode slurry.
[0061] [evaluation] (Peel strength test) The peel strength was measured using a micro autograph. First, the negative electrode structures of Comparative Example 1 and Examples 1 to 4 pressed with a linear pressure of 2.5 kN / cm in a roll press were punched out with a diameter of Φ14.5. Next, double-sided tape was attached to the sample stage of the micro autograph, and the current collector foil side of the punched negative electrode structure was attached to the top of the layer with the current collector foil side facing downward, and the coated surface was placed facing upward. In addition, double-sided tape of Φ11.28 was attached to the terminal side of the micro autograph. Then, the terminal was moved downward to the negative electrode structure, and the pressure at the time of contact was 50 N / cm. 2 Thereafter, the negative pressure was measured when the sample was moved upward, and the maximum value was taken as the peel strength.
[0062] (Battery performance test) The resistance change rate of the evaluation batteries prepared in Comparative Example 1 and Examples 1 to 3 was measured as follows. First, 100 cycles of charge and discharge (cycle test) were performed under conditions of 25°C, 2C, and SOC 93%-10%, and then the resistance value (resistance value before heating) was measured. Then, each evaluation battery after the cycle test was heated at 100°C for 6 hours, returned to room temperature, and the resistance value (resistance value after heating) was measured. The resistance change rate was calculated from the resistance value before heating and the resistance value after heating. The results are shown in Table 1. Note that when the resistance change rate is negative, it means that the resistance increased after heating, and when the resistance change rate is positive, it means that the resistance decreased after heating.
[0063] The evaluation batteries of Examples 2 and 4 were initially charged to 3.7 V and initially discharged at a rate of 5 C. The initial resistances were calculated from the voltage drop 5 seconds after the initial discharge and compared. The results are shown in Table 1.
[0064] [Table 1]
[0065] As shown in Table 1, the peel strength of all of Examples 1 to 4 is higher than that of Comparative Example 1, and it was confirmed that the electrode of the present disclosure suppresses peeling. From this, it is presumed that the increase in battery resistance is suppressed in the battery using the electrode of the present disclosure. Furthermore, in Examples 1 to 3, the resistance value was reduced (the resistance change rate increased) by heating after the cycle test compared to Comparative Example 1. It is considered that the resistance value was reduced because the fluorine-based lubricant that became liquid by heating was filled between the particles, and a good electron conduction path was maintained and restored. Furthermore, the initial resistance of Example 4 was better than that of Example 2. It is presumed that a good electron conduction path was formed by compounding the Si-based active material and the fluorine-based lubricant. [Explanation of symbols]
[0066] 1...Current collector 2...Active material layer 10... Electrode 11... Electrolyte layer 100... Secondary battery
Claims
1. It is used in an active material layer containing an active material and a sulfide solid electrolyte, A fluorine-based lubricant that is solid at 25°C.
2. 2. The fluorine-based lubricant according to claim 1, having a melting point of 120° C. or lower.
3. The fluorine-based lubricant according to claim 1, having a fluoropolyether structure.
4. An electrode having an active material layer and a current collector, The active material layer contains an active material, a sulfide solid electrolyte, and a fluorine-based lubricant, The fluorine-based lubricant is a fluorine-based lubricant according to any one of claims 1 to 3.
5. 5. The electrode of claim 4, wherein the active material and the solid fluorolubricant are composited.
6. 5. The electrode according to claim 4, wherein the ratio of said fluorine-based lubricant to said active material is 4% by weight or more and 12% by weight or less.
7. A secondary battery comprising the electrode according to claim 4.
Citation Information
Patent Citations
Manufacturing method of sheet for solid secondary battery and binder for solid secondary battery
JP2022121547A
Polymer solution, method of manufacturing film using same, and resin composition for nonaqueous electrolyte secondary battery
WO2019230140A1
Method for manufacturing or recycling member for electrochemical device, method for manufacturing electrochemical device, member for electrochemical device, and electrochemical device
WO2021132675A1
Electrode and electrochemical device
JP2018147887A
Nonaqueous electrolyte and secondary battery including the same
JP2018200866A